Needle electromyography for paramedical staff - Tanaka, Fumiaki; Miyaji, Yosuke; Sonoo, Masahiro (Neurological Therapeutics, 2020)
Although needle electromyography (needle EMG) is only performed by medical doctors, clinical laboratory technicians should be especially familiar with needle EMG, as well as other paramedical staff.Because the needle is thinner than the blood collection needle, the pain during the needle electromyography insertion is lighter than the blood sampling. However, if the subject complains of pain, it should be dealt with immediately, such as by changing the position of the needle tip. In order to reduce pain, it is important to keep the muscle length isometric, including during contraction. Hemorrhage is not frequent in needle EMG, but attention should be paid to the bleeding diathesis and antithrombotic medication.In needle EMG, spontaneous discharges at rest and discharges at voluntary contraction are observed. It is possible to evaluate the localized diagnosis of the extent, the quality and extent, and the distribution of the disorder, as well as the diagnosis of finding–specific diseases.It is not enough to perform the needle EMG simply as requested by the doctor who ordered it. It is recommended that the examiner perform “neuromuscular electrodiagnosis” by conducting a detailed questioning and neurological examination before the test to prepare the test plan and by changing the test content flexibly according to the test results.